Team of rivals : the political genius of Abraham Lincoln - Goodwin, Doris Kearns (New York : Simon & Schuster, 2005)
Presents an overview of the presidency of Abraham Lincoln, explaining the genius of his political savvy, and describes the context in which he assigned a cadre of his fiercest rivals as his closest cabinet advisors.
Includes bibliographical references and index.
Adult
Adult
Library Journal
Booklist starred
Publisher's Weekly
Keywords: Lincoln, Abraham, -- 1809-1865.; Political leadership -- United States -- Case studies; Genius -- Case studies; Lincoln, Abraham, -- 1809-1865 -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 1861-1865.; Lincoln, Abraham, -- 1809-1865.; Leadership -- Case studies; Genius -- Case studies; Lincoln, Abraham, -- 1809-1865 -- Friends and associates; Presidents -- United States -- Biography; United States -- Politics and government -- 1861-1865, Civil War